The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.2500/aap.2011.32.3485
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency as a risk factor for allergic disorders and immune mechanisms

Abstract: Vitamin D deficiency (VDD) has been reported in very high rates in the U.S. population. Deficiency has been implicated in various diseases such as diabetes, high blood pressure, cardiovascular disease, and many cancers. It has also been implicated in several allergic disorders and immune system dysregulation. The National Health and Nutrition examination survey (NHANES) in 2005-2006 was a cross-sectional survey performed in the noninstitutionalized population of the United States by the Center for Disease Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 0 publications
1
34
0
2
Order By: Relevance
“…In a large survey conducted in USA, vitamin D deficiency was found to be positively correlated with prevalence of allergies (Frieri & Valluri 2011). Also there are several case-control studies showing higher rates of vitamin D deficiency among allergic patients than in controls (Ozkara et al 2012;Allen et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a large survey conducted in USA, vitamin D deficiency was found to be positively correlated with prevalence of allergies (Frieri & Valluri 2011). Also there are several case-control studies showing higher rates of vitamin D deficiency among allergic patients than in controls (Ozkara et al 2012;Allen et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, a considerable number of studies had been conducted linking vitamin D deficiency with autoimmune diseases and allergic disorders (Munger et al 2006;Frieri & Valluri 2011;Allen et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these cells, mast cells and lymphocytes are particularly key players in the pathogenesis of allergic rhinitis (15). Previous studies have shown that serum vitamin D levels are inversely related to allergic rhinitis [16,17].…”
Section: Introductionmentioning
confidence: 99%